Social Discrimination in Antology of Poetry Essay Atas Nama Cinta Written by Denny Ja (Content Analysis Research) - Septiaji, Aji (Jurnal Penelitian Humaniora, 2018)
Essay poetry is regarded as a matter of thinking and experience of social conditions in society nowadays. Although it has different role in the variety of literary form, it can be well received by society. Essay poetry should consist of three conditions, namely (1) essay poetry explores the inner side of an individual who is in a social conflict; (2) essay poetry using language that is easily understood; and (3) essay poetry is fiction. It may tell about real characters based on the history. However, the reality enriched with various fictional and dramatic figures that the essay poetry emphasizes is a reflection and moral content conveyed through a story, not merely an accurate portrait of history. The research method used is qualitative through content analysis technique. The data were collected based on anthology of poetry essay Atas Nama Cinta written by Denny JA. Through this poetry essay, it will be examined on social issues such as discrimination experienced by humans in general, such as discrimination against different religions, gender, Chinese, and others. The stories that are presented seem to open the knowledge about the other side of the human love story that commonly romantic and cheerful. The social and cultural conditions of discrimination embrace society in a real way. In fact, this reflects social conditions of society in general in the era of globalization and information.Keywords: discrimination, social, essay poetry